2013
DOI: 10.1007/s11031-013-9365-2
|View full text |Cite
|
Sign up to set email alerts
|

Flow experience and team performance: The role of team goal commitment and information exchange

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 65 publications
3
73
1
1
Order By: Relevance
“…However, this does not rule out the possibility that the interaction of the affiliation motive and social relatedness satisfaction can play a crucial role in predicting flow in sports in which social relatedness is more important. Examples are recreation-oriented fitness sports courses, which are partly performed for the sake of spending harmonious leisure time with other people (e.g., and team sports in which the harmonious interplay is a defining characteristic (for flow in team sports, see Aube, Brunelle, & Rousseau, 2014; for flow in nonachievement situations, see Schiepe-Tiska & Engeser, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, this does not rule out the possibility that the interaction of the affiliation motive and social relatedness satisfaction can play a crucial role in predicting flow in sports in which social relatedness is more important. Examples are recreation-oriented fitness sports courses, which are partly performed for the sake of spending harmonious leisure time with other people (e.g., and team sports in which the harmonious interplay is a defining characteristic (for flow in team sports, see Aube, Brunelle, & Rousseau, 2014; for flow in nonachievement situations, see Schiepe-Tiska & Engeser, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Across different domains, previous studies have consistently argued that there is a significant role for intrinsic motivation in producing adaptive outcomes (e.g., Keller and Bless, 2008; Aubé et al, 2014; Cerasoli and Ford, 2014). To be specific, it was found that optimal challenge can lead to more attention devoted, greater persistence and stronger determination, all of which are beneficial to the improvement of task performance (Aubé et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Ryan et al (2006) suggested that one's intrinsic motivation was significantly associated with enjoyment. It was also found that optimal challenge can result in more attention devoted, greater persistence and determination (Aubé et al, 2014). Thus, we predict participants to enjoy more, invest greater effort and care more about task performance in the near miss condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow at work has previously been found to be cross-sectionally associated with performance among music teachers (Bakker, 2008) and in a smaller sample of different occupations (Eisenberg et al, 2005;Demerouti, 2006), and students who frequently experience flow perform better (Shernoff et al, 2003;Engeser & Rheinberg, 2008;Aubé, Brunelle & Rousseau, 2014). Some of these studies have also found that the association between flow and performance is conveyed by the degree to which employees feel they are able to succeed in mastering challenges (Engeser & Rheinberg, 2008), focus and direct their efforts towards work goals and relevant actions (Demerouti, 2006), and the desire to achieve high goals (Eisenberger et al, 2005).…”
Section: Organisation Of Workmentioning
confidence: 97%